Coordination Polymer Electrocatalysts Enable Efficient CO‐to‐Acetate Conversion. Issue 10 (16th January 2023) - Luo, Mingchuan; Ozden, Adnan; Wang, Ziyun; Li, Fengwang; Erick Huang, Jianan; Hung, Sung‐Fu; Wang, Yuhang; Li, Jun; Nam, Dae‐Hyun; Li, Yuguang C.; Xu, Yi; Lu, Ruihu; et al.
Abstract: Upgrading carbon dioxide/monoxide to multi‐carbon C2+ products using renewable electricity offers one route to more sustainable fuel and chemical production. One of the most appealing products is acetate, the profitable electrosynthesis of which demands a catalyst with higher efficiency. Here, a coordination polymer (CP) catalyst is reported that consists of Cu(I) and benzimidazole units linked via Cu(I)‐imidazole coordination bonds, which enables selective reduction of CO to acetate with a 61% Faradaic efficiency at −0.59 volts versus the reversible hydrogen electrode at a current density of 400 mA cm −2 in flow cells. The catalyst is integrated in a cation exchange membrane‐based membrane electrode assembly that enables stable acetate electrosynthesis for 190 h, while achieving direct collection of concentrated acetate (3.3 molar) from the cathodic liquid stream, an average single‐pass utilization of 50% toward CO‐to‐acetate conversion, and an average acetate full‐cell energy efficiency of 15% at a current density of 250 mA cm −2 . Abstract : Integrating a coordination polymer catalyst consisting of Cu(I) and benzimidazole units linked via Cu(I)‐imidazole coordination bonds in a cation exchange membrane‐based membrane electrode assembly enables stable acetate electrosynthesis for 190 h, while achieving direct collection of concentrated acetate, an average single‐pass utilization of 50%, and an average acetate full‐cell energy efficiency of 15% at 250 mA cm −2 .